Optimization and validation of blade parameters for inter-row weeding wheel in paddy fields - Zhang, Yongzheng; Tian, Liang; Cao, Chengmao; Zhu, Chengliang; Qin, Kuan; Ge, Jun (Frontiers in Plant Science, 2022)
The performance of existing rice-paddy weeding machines is not optimal. In this study, the influence of the installation angle of the weeding-wheel blade on cutting resistance and soil-slippage ability was analyzed. The optimal blade angle of the weeding wheel (i.e., the angle at which the resistance to the weeding wheel is minimal and the disturbance speed of the soil maximal) was shown to be < 20°; numerical simulation showed the actual optimal value to be 0°. Different weeding depths (30, 40, and 50 mm), rotation speed of weeding wheel (120, 180, and 240 r/min), and weeder forward speeds (0.3, 0.6, and 0.9 m/s) were used as test factors, and the rates of seedling injury and weeding were used as performance-evaluation criteria to optimize the machine in a secondary orthogonal-rotation combination test. Field experiments showed that the weeding wheel can exhibit optimal working performance under the operating conditions of weeding depth of 39 mm, rotation speed of 175 r/min, and forward speed of 0.6 m/s. The seedling injury and weeding rates were 4.4% and 88.2%, respectively, which were consistent with the numerically predicted results and met the agronomic requirements. This study provides a technical reference for the improvement of paddy-field weeding components.